The effects of heavy metal on growth and mitochondrial changes in the Cajanus cajan - Sujatha, B.; Priyadarshini, B. (Current Botany, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> This study was carried out to determine the effects of heavy metal (Pb and Cd) on growth, relative growth index, tolerance index and ultrastructural alterations of mitochondria in pigeonpea cultivars. The results showed that enhanced concentrations of Pb and Cd decreased the growth, relative growth index, tolerance index of pigeonpea cultivars. Further the ultrastructural studies revealed alterations in the mitochondrial structures in both the cultivars in response to heavy metals.